2004
DOI: 10.1093/jn/134.4.980s
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Peptides from Milk Proteins

Abstract: Hypertension is the major controllable risk factor associated with cardiovascular disease (CVD) events such as myocardial infarction, stroke, heart failure, and end-stage diabetes. A 5 mm Hg decrease in blood pressure has been equated with approximately 16% decrease in CVD. In the U.S. alone current annual antihypertensive drug costs are approximately dollars 15 billion. The renin-angiotensin-aldosterone system is a target for blood pressure control. Cleavage of angiotensinogen by renin produces angiotensin I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
443
1
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 618 publications
(454 citation statements)
references
References 78 publications
5
443
1
5
Order By: Relevance
“…In addition, in a recent placebo-controlled trial in 135 mildly hypertensive subjects by Engberink et al no effects of milk-derived peptides on blood pressure, ACE activity or plasma angiotensin II concentrations were found after 8 weeks of treatment (64) . Also, bioavailability of these peptides is questionable (58) , although one study has demonstrated the uptake of intact lactotripeptides (65) . Finally, the amount of Dairy consumption and the metabolic syndromeACE-inhibitory peptides in non-enriched dairy products may simply be too low to play a significant role in blood pressure regulation.…”
Section: Effects Of Bioactive Peptides On Blood Pressure and Coagulationmentioning
confidence: 99%
“…In addition, in a recent placebo-controlled trial in 135 mildly hypertensive subjects by Engberink et al no effects of milk-derived peptides on blood pressure, ACE activity or plasma angiotensin II concentrations were found after 8 weeks of treatment (64) . Also, bioavailability of these peptides is questionable (58) , although one study has demonstrated the uptake of intact lactotripeptides (65) . Finally, the amount of Dairy consumption and the metabolic syndromeACE-inhibitory peptides in non-enriched dairy products may simply be too low to play a significant role in blood pressure regulation.…”
Section: Effects Of Bioactive Peptides On Blood Pressure and Coagulationmentioning
confidence: 99%
“…Most intensively studied are the tripeptides ValPro-Pro (VPP) and Ile-Pro-Pro (IPP), both with documented ACE-inhibitor effect in vitro. [8][9][10] Furthermore, FM contains proteins with opioid-like effect and possibly also g-amino butyric acid, which has been shown to have an inhibitory effect on the sympathetic nervous system in spontaneously hypertensive rats. 11,12 The type and amount of the antihypertensive compounds in FM depends on the substrate (milk) and the lactobacilli strain used for fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Pepsin and trypsin are commonly applied in enzymatic hydrolysis of proteins. They are generally used to produce ACE inhibitory peptides, namely antihypertensive peptides and calcium-binding phosphopeptides [Adt et al 2011, FitzGerald et al 2004. Other digestive enzymes and combinations of various proteinases, including alcalase, chymotrypsin, pancreatin Information adapted from references: Carrasco-Castilla et al [2012], Pihlanto [2006, 2007], Langevin et al [2012], Minkiewicz and Dziuba [2009].…”
Section: Strategy For Isolating and Analysing Bioactive Peptidesmentioning
confidence: 99%
“…The exact amount of a peptide that can be released and activated during the consumption of a balanced diet remains unknown because proteolytic enzymes are characterised by varied specifi city, therefore, the range of bioactive fragments released from a precursor protein cannot be accurately predicted [Dziuba and Darewicz 2007, Dziuba et al 2006, Phelan et al 2009]. The presence of bioactive peptides in dairy products such as cheese, fermented milk and yoghurt has been reported in numerous research studies [FitzGerald et al 2004, Gagnaire 2001, Gobbetti et al 2002, Korhonen and Pihlanto 2006, Meisel et al 1997, Nakamura et al 1995, Saito et al 2000.…”
Section: Introductionmentioning
confidence: 99%